THE INFLUENCE OF WORK ENVIRONMENT: PSYCHOSOCIAL AND PHYSICAL ASPECTS ON EMPLOYEE PERFORMANCE AT BANK MANDIRI TASPEN MANADO AREA - George, Calvin; Lapian, S.L.H.V. Joyce; Rogi, Mirah H. (Universitas Sam Ratulangi, 2026)
Employee performance plays a crucial role in determining the success and sustainability of banking institutions. This study examines the influence of the work environment, specifically psychosocial and physical aspects, on employee performance at Bank Mandiri Taspen Manado Area. A quantitative research method was applied, with data collected using questionnaires distributed to 34 employees. Multiple linear regression was used to analyze the relationship between the variables. The findings indicate that both psychosocial and physical work environment factors have a positive and significant effect on employee performance, either partially or simultaneously. A supportive psychosocial environment characterized by positive communication, interpersonal relationships, and fair leadership enhances motivation and work morale. Meanwhile, an adequate physical environment including lighting, workspace layout, noise control, and ventilation contributes to employee comfort and work efficiency. These results highlight the need for organizations to invest in creating both healthy social interactions and physically conducive working conditions to optimize employee performance and overall productivity. The study concludes that improving workplace conditions is a strategic approach to strengthening employee well-being and enhancing banking service outcomes. Keywords: Psychosocial Work Environment, Physical Work Environment, Employee Performance